Potential Utility of Metal-Organic Framework-Based Platform for Sensing Pesticides - Vikrant K.; Tsang D.C.W.; Raza N.; Giri B.S.; Kukkar D.; Kim K.-H. (My University, 2025)
The progress in modern agricultural practices could not have been realized without the large-scale contribution of assorted pesticides (e.g., organophosphates and nonorganophosphates). Precise tracking of these chemicals has become very important for safeguarding the environment and food resources owing to their very high toxicity. Hence, the development of sensitive and convenient sensors for the on-site detection of pesticides is imperative to overcome practical limitations encountered in conventional methodologies, which require skilled manpower at the expense of high cost and low portability. In this regard, the role of novel, advanced functional materials such as metal-organic frameworks (MOFs) has drawn great interest as an alternative for conventional sensory systems because of their numerous advantages over other nanomaterials. This review was organized to address the recent advances in applications of MOFs for sensing various pesticides because of their tailorable optical and electrical characteristics. It also provides in-depth comparison of the performance of MOFs with other nanomaterial sensing platforms. Further, we discuss the present challenges (e.g., potential bias due to instability under certain conditions, variations in the diffusion rate of the pesticide, chemical interferences, and the precise measurement of luminesce quenching) in developing robust and sensitive sensors by using tailored porosity, functionalities, and better framework stability. © 2018 American Chemical Society.